Preparation and Characterization of a Hierarchically Porous Zeolite-Carbon Composite from Economical Materials and Green Method - Ibrahim, Nargis H.; Al-Jubouri, Sama M.; Alfutimie, Abdullatif (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
A hierarchically porous structured zeolite composite was synthesized from NaX zeolite supported on carbonaceous porous material produced by thermal treatment for plum stones which is an agro-waste. This kind of inorganic-organic composite has an improved performance because bulky molecules can easily access the micropores due to the short diffusion path to the active sites which means a higher diffusion rate. The composite was prepared using a green synthesis method, including an eco-friendly polymer to attach NaX zeolite on the carbon surface by phase inversion. The synthesized composite was characterized using X-ray diffraction spectrometry, Fourier transforms infrared spectroscopy, field emission scanning electron microscopy, energy dispersive X-ray analysis, thermogravimetric analysis, N2-adsorption/desorption isotherm, and point of zero charges. The results showed that the composite had a surface area of 208.463 m2/g, a pore volume of 0.122 cm3/g, distinct morphology, and functional groups. Also, its pHpzc was 6.9 above which its surface has a positive charge and below 6.9 it is charged negatively. This property determines the composite sorption property in the removal of pollutants from wastewater.